Kebutuhan Dasar Manusia dalam Perspektif Pendidikan Islam - sada, heru juabdin (Universitas Islam Negeri Raden Intan Lampung, 2017)
Needs are something that is needed by humans to reach the level of well-being, so that if human needs are not met properly, then their human beings will not feel prosperous. It can be said that needs are something that must be there, because without that our lives become less prosperous or at least less prosperous. There are five basic human needs as stated by Abraham Maslow, the need for self-actualization, self-esteem needs, the need for love and the need for affection, the need for security and the need for comfort and need. In Islam, looking at the most basic human needs is an absolute obligation that must be lived and fulfilled among them needs: Dharuriyat Needs (i) the need to maintain religion: hold fast to religion, learn it, then preach it, stay away and warn of shirk and riya '; Combating apostates; Reminiscent of bid'ah actions and against ahlul bid'ah. (ii). self-care needs: in an emergency (forced), can eat any food for survival, even though only something that is available at the origin is available; Fulfill basic basic needs, such as food, drinks and clothing; (iii) moral requirements. (iv) guarding offspring; Prompts for marriage; witness in marriage; must maintain and provide for the child, the obligation to ensure children's education; Forbid marriage with adulterers; Forbid thalaq unless forced and forbid ikhtilâth. (v) safeguarding property: Islam requires Muslims to do charity and endeavor; Maintain property in their power; Islamic religion advocates for bershadaqah, justifying buying and selling and debts; Islamic religion forbids all forms of tyranny against other Muslim rights and property and must replace them; Obligation to safeguard property and not waste it.